Genetic Study for the Role and Predictive Consequence of Certain Cytokines in Hepatitis B Iraqi Patients - Ali Hussein Al-Marzoqi (Journal of Global Pharma Technology, 2017)
Hepatitis B virus (HBV) infection is a serious and common infectious disease of the liver, HBV infection is endemic, particularly in developing countries, and is a serious public health problem. Cytokines and regulatory molecules play a fundamental role in the immuno pathogenesis of HBV infection. The gene loci for cytokines are defined, and polymorphisms of these genes are suggested to influence the outcome of HBV infection. In our study we revealed that there are elevated in Aspartate transaminase (AST), Alanine transaminase (ALT) and Bilirubin (Bil) among HBV patient than control group. IL–4 rs2070874 SNP Genotypes among patients with HBV was ONLY 68 positive to PCR results while in contrast it is only 9 within control group. The highest ratio of genotype in both groups was in CC as 36 (52.9%) in patients and 5 (55.6%) in control. Allele frequency on other hands describe as follow;  in HBV and control group for C 72 (63.7%), 11 (61.1%) while for T 41 (26.3%) and 7 (38.9%) respectively. Genotypes of IL–10 rs1800872SNP among patients was in AA as 43 (62.3%) in patients and 13 (76.5%) in control. On other hands Allele frequency describe as follow; in HBV and control group for A 106 (76.8%), 29 (85.3%) while for G 32 (23.2%) and 5 (14.7%). IFN-γ (rs2069705 SNP) Genotypes among patients with HBV was in AG as 39 (28.8%) in patients and 10 (47.6%) in control with GG. Allele frequency. Moreover, describe as follow; in HBV and control group for A 61 (33.3%), 28 (66.7%) while for G 122 (66.7%) and 28 (66.7%)Keywords: Hepatitis, Cytokines, PCR, IFN, SNPs, IL-10, IL-2.